2017
DOI: 10.1016/j.ijlp.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A psycho-legal perspective on sexual offending in individuals with autism Spectrum disorder

Abstract: It is important to consider whether there are innate vulnerabilities that increase the risk of an individual with an autistic spectrum disorder (ASD), predominantly those defendants with a diagnosis of Asperger's Syndrome, being charged and convicted of a sexual offence. The significance of such can be readily seen in recent English case law, with judgments on appeal finding convictions unsafe where there have been a number of failings in the Judge's summing up. In this article, we will consider the gravity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
(46 reference statements)
0
6
0
3
Order By: Relevance
“…However, in many cases a prison sentence is not appropriate (e.g., Allely, 2015aAllely, , 2015b. Greater awareness and understanding of these ASD impairments are important to distinguish ASD symptomology from sexual perversion and informing appropriate treatments (Mouridsen, 2012), in addition to avoiding unjust harsh sentencing (Freckelton, 2009(Freckelton, , 2013Allely & Creaby-Attwood, 2016;Creaby-Attwood & Allely, 2017). Lastly, Sheldon and Howitt (2007) and many others have highlighted the issues surrounding the appropriateness of conventional sex offender treatment programmes for child pornography offenders on the basis that they 34 have different risks and needs to contact child sexual offenders.…”
Section: Resultsmentioning
confidence: 99%
“…However, in many cases a prison sentence is not appropriate (e.g., Allely, 2015aAllely, , 2015b. Greater awareness and understanding of these ASD impairments are important to distinguish ASD symptomology from sexual perversion and informing appropriate treatments (Mouridsen, 2012), in addition to avoiding unjust harsh sentencing (Freckelton, 2009(Freckelton, , 2013Allely & Creaby-Attwood, 2016;Creaby-Attwood & Allely, 2017). Lastly, Sheldon and Howitt (2007) and many others have highlighted the issues surrounding the appropriateness of conventional sex offender treatment programmes for child pornography offenders on the basis that they 34 have different risks and needs to contact child sexual offenders.…”
Section: Resultsmentioning
confidence: 99%
“…This led them to conclude that there is insufficient support for the previous evidence which had indicated that individuals with ASD are more likely to engage in sexual offending behaviour or sexually harmful behaviour. While there have been some studies that have found that individuals with ASDs are no more likely to commit sexual offending behaviour when compared to the general population, some research highlights the importance of recognising that, in individuals with ASD impairments in social functioning and engagement in addition to a desire for attachment or sexual intimacy with others, the challenges they face may lead to sexually inappropriate and harmful behaviour (Murrie et al, 2002;Sevlever et al, 2013;Allely and Creaby-Attwood, 2016;Creaby-Attwood and Allely, 2017). Murrie et al (2002) describe six case studies of individuals with ASD who engaged in harmful sexual behaviour.…”
Section: Autism Spectrum Disorder and Sexual Offending Behaviourmentioning
confidence: 99%
“…For example, individuals with autism are considered stalking while they are actually trying to be social (Mintah & Parlow, 2018). Similarly, when individuals with autism try to calm down by stimming, it is often assumed that sexual stimulation is taking place (Creaby-Attwood & Allely, 2017).…”
Section: Public Misconceptionmentioning
confidence: 99%